Association of Left Atrial Enlargement and Atrial Fibrillation With Cognitive Function and Decline: The ARIC‐NCS - Michael J. Zhang; Faye L. Norby; Pamela L. Lutsey; Thomas H. Mosley; Rebecca J. Cogswell; Suma H. Konety; Tze‐Fan Chao; Amil M. Shah; Scott D. Solomon; Alvaro Alonso; Lin Y. Chen (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2019)
Background Atrial fibrillation (AF) is associated with cognitive decline. Whether left atrial enlargement (LAE), a critical substrate for AF, is also associated is less well established. Therefore, we assessed the association of LAE and AF with cognitive decline in the ARIC‐NCS (Atherosclerosis Risk in Communities Neurocognitive Study). Methods and Results Participants (n=3391; mean age, 75±5 years; 59% women) underwent cognitive tests and 2‐dimensional echocardiograms at visit 5 (2011–2013) and follow‐up cognitive tests at visit 6 (2016–2017). LAE was defined as left atrium volume index ≥34 mL/m2. AF was ascertained using study ECGs and hospitalization discharge codes. We assessed the association of AF and LAE with (a) cognitive domain scores at visit 5 and (b) cognitive domain score changes between visit 5 and visit 6. At visit 5, compared with the reference group (without AF, normal left atrium), participants with LAE and AF had significantly lower global cognition (Z score, −0.24; 95% CI, −0.38 to −0.10), whereas participants with AF and without LAE and participants with LAE and without AF did not have lower global cognition. In longitudinal analysis, compared with the reference group, participants with AF but without LAE had significantly greater decline in global cognition (Z score, −0.13; 95% CI, −0.21 to −0.06). However, LAE, with or without AF, was not associated with greater cognitive decline. Conclusion Although LAE with AF was significantly associated with lower cognitive function in cross‐sectional analysis, LAE, with or without AF, was not associated with greater cognitive decline over 5 years, highlighting the importance of evaluating longitudinal cognitive function. Future studies should have longer follow‐up and evaluate left atrium function.